Beauty and Morality in Yuriko Saito: An approach from the Emotionalist Functionalism of David Hume - Godoy Domínguez, M.ª Jesús (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
In this paper, we will try to study the aesthetic-moral judgments established by Yuriko Saito in the recent field of everyday aesthetics, in light of the functionalist beauty of the enlightened thinker David Hume. For this aim, we unravel the affective mechanism on which the aesthetic experience rests both in the case of the irrelevant everyday object on which Saito theorizes, and in the case of the utilitarian object on which Hume runs. This mechanism shows that in both thinkers the judgment of taste is only one with moral judgment. It is thus concluded that the sympathy by which there is beauty in the young Hume, as it ends up turning towards premature empathy in the last Hume, reinforces the connection with Saito, with her concern for the other and her desire to make the world a better place.